2014
DOI: 10.4304/jnw.9.8.2129-2136
|View full text |Cite
|
Sign up to set email alerts
|

Regression-Based Microblogging Influence Detection Framework for Stock Market

Abstract: Microblogs and social networks have become a valuable resource for mining sentiments in various fields. The sentiments posted on the web have reportedly influenced the trading and investment decisions and activities taking place in the stock exchanges. In this study, we have investigated explored the effects of microblogs on Chinese Stock Market. We have particularly focused on whether measurements of collective mood states (sentiments and persuasions) derived from large-scale microblogging posts are correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Behavioral finance has proven that financial decisions are clearly driven by emotions (Rubbaniy, Asmerom, Rizvi, & Naqvi, 2014). The sentiments of reviews posted on social media reportedly affect trading, investment decisions, and activities in the stock exchanges, and thus become a valuable resource (Zhu et al, 2014). In recent years, significant progress has been made in sentiment tracking techniques that directly extract public sentiments from social media content.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Behavioral finance has proven that financial decisions are clearly driven by emotions (Rubbaniy, Asmerom, Rizvi, & Naqvi, 2014). The sentiments of reviews posted on social media reportedly affect trading, investment decisions, and activities in the stock exchanges, and thus become a valuable resource (Zhu et al, 2014). In recent years, significant progress has been made in sentiment tracking techniques that directly extract public sentiments from social media content.…”
Section: Related Workmentioning
confidence: 99%
“…With the rise of social media and the promotion of relevant platforms for user-generated content, user opinions have begun to play a greater role in the stock market. Zhu et al (2014) reported in 2008 that about 25% of adults are indirectly dependent on investment advice spread through social media. In response to the increase in online news and social media, web-mining-based forecasting methods have been extensively studied to improve the performance of financial market forecasts (Xu, Li, Jiang, & Cheng, 2012).…”
Section: Predict Stock Prices Using Social Media Miningmentioning
confidence: 99%
See 2 more Smart Citations